An advantageous level of irrigation water salinity for wheat cultivation (Journal of the Bangladesh Agricultural University, 2014)
Response of wheat (Triticum aestivum L., cv. Shatabdi) to irrigation water of five salinity levels was investigated at the Bangladesh Agricultural University (BAU) farm with a view to search for a possible advantageous salinity level for the crop. The experiment comprised five treatments ? I1: irrigation by fresh water of background salinity 0.385 dS m?1 (control) and I2 ? I5: irrigation by synthetic saline water (prepared by mixing sodium chloride salt with fresh water) of electrical conductivity (EC) 4, 7, 10 and 13 dS m?1 (at 25oC), respectively. Wheat was grown under three irrigations applied at maximum tillering, booting and milking/grain filling stages, and with recommended fertilizer dose. Irrigation water of EC ?10 dS m?1 significantly (p = 0.05) suppressed most growth and yield attributes, and yield of wheat compared to irrigation by fresh water (I1). An attention-grabbing observation was that irrigation by saline water of 4 dS m?1 (I2) contributed positively to the crop attributes. Leaf area index (LAI), spike length, spikelets and grains per spike, 1000-grain weight and above ground dry matter (ADM) of wheat increased by 1.9?3.4, 0.9, 2.6, 7.4, 2.1 and 2.8?6.0%, respectively in I2 compared to the control. The improvement in the LAI and ADM in I2 was significant over I1. Because of the largest spike density, the utmost grain (3.85 t ha?1), straw (5.09 t ha?1) and biomass (8.93 t ha?1) yields of wheat were however obtained under I1. The proposition of the advantageous irrigation water salinity level of 4 dS m?1 thus warrants further investigation DOI: http://dx.doi.org/10.3329/jbau.v11i1.18225 J. Bangladesh Agril. Univ. 11(1): 141-146, 2013